INFORMATION SOCIETY, DEVELOPMENT OF ICTS (INFORMATION AND COMMUNICATION TECHNOLOGIES), AND NEW ECONOMY - Fardiah Lubis (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang, 2017)
Abstract Information society is fairly regarded as a society where information holds an important role in people’slife. This statement brings about a query whether the society that we are currently living now can be regarded as one.While some scholars may agree upon this notion, some may not. Their point of views are described in this paper tosomewhat respond to the query. Information society is commonly connected with the development of ICTs (Information andCommunication Technologies) and it is the impact of them on economy, particularly, that will be discussed furtherin this paper. The so called new economy emerged as a result of development of ICTs. Internet as one of the ICTsproduct gives way to the development of e-commerce. However with its shortcomings, it is arguable that there arestill more work to be done in order to obtain the benefit that development of ICTs can bring to the society.Key words: Information Society, ICT, New Economy, E-commerce